Your body battles a broken bone - Cobb, Vicki; Harris, Andrew, 1977-; Kunkel, Dennis (Minneapolis, MN : Millbrook Press, 2009)
Comic illustrations and photomicrographs describe how the body heals a broken bone.
Includes bibliographical references (p. 31-32) and index.
5.2
3-6
Keywords: Bones -- Wounds and injuries -- Juvenile literature; Bones -- Wounds and injuries; Bones -- Wounds and injuries